Estratégias metodológicas de educação física na escola especial e o processo de inclusão de alunos com deficiência na educação básica comum - Dalla Déa, Vicente Paulo Batista (2019)
This study has as general objective to verify the contents and pedagogical practices in the Physical Education classes, present in the special school, that could favor the inclusive education in the regular school of basic education. Its specific objectives are: to analyze guiding documents and materials / equipment used in Physical Education classes in the special school; to observe the methodological processes and the necessary knowledge for the practice of Physical Education in the special school; to verify whether special school actions can reverberate in the process of including pupils with disabilities in regular basic education. This is a qualitative research carried out using the participant observation technique with field journal record. A semistructured interview was carried out with the nine physical education teachers of the research institution. Three (3) classes of each of these nine teachers were observed, focusing on the methodological process based on the conceptions of Physical Education, contents covered, materials, spaces and assistive technologies present in them. As an educational product of this work, we will make a "Guide to guidelines for promoting inclusion in the Physical Education School" with the intention of contributing to inclusion in Regular Education, especially in Physical Education classes, based on the reality lived in the Special School. Through the results of the classroom observations and interviews it was possible to verify that some actions favor the inclusion of students with disabilities in regular education, some of them: shorter class time, lower number of students per class, more attractive materials, repetition of contents , a case study with students with disabilities and family participation.